2018
DOI: 10.21580/pjpp.v3i1.2489
|View full text |Cite
|
Sign up to set email alerts
|

What Millennials Want: How to Optimize Their Work

Abstract: <p><strong>Abstract:</strong> It is known that it is quite difficult for companies to create a working environment that suits the characters of the Millennials, who are now undoubtedly make up the largest proportion of the workforce. This study aims to understand how job autonomy and boredom at work affect Millennials’ work engagement. Using non-probability sampling methods, 320 Millennial employees (19–37 years old) from various organizations (private and public organization) in Indonesia ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
0
18
0
4
Order By: Relevance
“…While efforts have been made to lessen the effect of the common method bias, more could be done to minimize these biases. Future research can obtain better and even more comprehensive data by combining several data collection methods such as questionnaires and interviews (Forastero, Sjabadhyni, & Mustika, 2018). Secondly, this study uses a cross-sectional research design, which assesses respondents only once at a particular point in time.…”
Section: Limitationsmentioning
confidence: 99%
“…While efforts have been made to lessen the effect of the common method bias, more could be done to minimize these biases. Future research can obtain better and even more comprehensive data by combining several data collection methods such as questionnaires and interviews (Forastero, Sjabadhyni, & Mustika, 2018). Secondly, this study uses a cross-sectional research design, which assesses respondents only once at a particular point in time.…”
Section: Limitationsmentioning
confidence: 99%
“…In one of private banks' headquarter in Jakarta, Azizah and Ratnaningsih (2018) found that generation Y's level of work engagement is mostly high. In their research among generation Y in national private, multinational private, and public sector, Forastero, Sjabadhyni, & Mustika (2018) found that most of generation Y have worked for three to six years, as opposed to less than three years.…”
Section: Resultsmentioning
confidence: 99%
“…Untuk itu perlu diketahui bahwa karyawan usia muda dengan usia produktif memiliki karakteristik yang berbeda dengan generasi karyawan yang lebih senior. Penelitian terbaru mengenai keterikatan kerja (work engagement) pada karyawan generasi milenial, menunjukkan bahwa kebosanan kerja dan kemandirian kerja berperan dalam memengaruhi keterikatan kerja (Forastero, Sjabadhyni, & Mustika, 2018). Hasil penelitian ini menunjukkan bahwa kemandirian kerja (job autnomy) memiliki peran yang penting dalam meningkatkan keterikatan kerja dan dapat menurunkan kebosanan kerja.…”
Section: │ 233unclassified